Features of advertising of intellectual property objects - Veres Somosi, Mariann; Tkachova, N. P.; Pererva, P. G. (ТОВ "Юридична компанія "Юрсервіс", 2023)
Advertising of intellectual property refers to the introduction of an invention, a utility model, an industrial model of a product or the use of a method protected by a patent into commercial circulation. In patent law, the most important concept determining patentability is novelty, i.e., prior art uncertainty, which includes all information that has become publicly available in the world prior to the filing date. Advertising can be a means of their disclosure of information, on the basis of which novelty is determined, and in relation to invention - and inventive level. You can advertise that a product is protected by a patent only if it is true. Otherwise, such advertising will be unreliable and will be considered an act of unfair competition. To create high-quality advertisements, you need to make some creative efforts.
Особливості реклами об’єктів інтелектуальної власності
Keywords: intellectual property; advertising; market; commercialization; transfer; enterprises